ANALISIS PERUBAHAN TARIF PENGHASILAN TIDAK KENA PAJAK (PTKP) TAHUN 2015 DAN TAHUN 2016 TERHADAP PENERIMAAN PAJAK PENGHASILAN (PPH) PASAL 21 DI KANTOR PELAYANAN PAJAK PRATAMA BITUNG - Lewa, Megawani; Kalangi, Lintje; Pontoh, Winston (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Tax is a compulsory payment to every citizen whose counterpart is not direct. In 2016 there is an Increase in the tariff of Non Taxable Revenue (PTKP). The increase of non-taxable income (PTKP) will be enjoyed by the people who work as employees/employees, and the Taxpayer Object Tax (WPOP) workers who have free and / or self-employed jobs because it will lower taxable income tax (PKP) taxpayers. However, the increase in PTKP has the potential to decrease income tax revenue. This study aims to evaluate the effect of PTKP changes on the acceptance of Income Tax Article 21 in KPP Pratama Bitung. The method used is qualitative descriptive method. The research results show that the non-taxable income (PTKP) experienced a 50% increase and this affects income tax revenue PPh) significantly. Expected to be able to do things to increase tax revenue from the income tax side of article 21. One of them is to adjust the limits of PTKP with the lowest salary / income of employees. In addition, the Tax Office of Bitung Pratama is also expected to provide continuous supervision and extension on taxpayers of individuals, bodies and treasurers of government offices concerning the awareness of their obligation to withhold tax on income tax on the employee or employees accordingly at the prevailing rate.Keywords: Non Taxable Income, Income Tax, Changes receipts